Enzymatic Combustion by Ligninolytic Enzymes of Lignicolous Fungi - Nagadesi, Praveen Kumar; Arya, Arun (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Lignicolous fungi are wood degrading organisms, which were able to decompose all wood polymers; lignin, cellulose and hemicellulose etc. by producing ligninolytic, cellulolytic and hemicellulolytic enzymes respectively. The complex plant polymer like lignin was biodegraded by a unique “enzymatic combustion,” i.e. a nonspecific enzyme-catalyzed burning. Enzymatic combustion, involves oxidative extracellular enzymes. The selective lignicolous fungi that decompose preferentially wood lignin by lignin peroxidase, Manganese peroxidase, and laccases in wood polysaccharides leaving cellulose were Lenzites sterioides1, 2, L. betulina, L. exima, Phellinus gillvus, P. nilgheriensis, P. robustus, Flavodon flavum, Ganoderma lucidum, Shizophyllum Commune. The soft rot fungi mainly cause degradation of cellulose by producing cellulolytic enzyme were Phoma multirostrata, Theliviopsis stste of Ceratocystis paradoxa, Fusarium palidoroseum, Alternaria Alternata, Chaetomium globosum, Curvularia lunata, Rhizopus stolonifer, Trichoderma Viride. In order to determine the lignin degrading capability of different lignicolus fungi from Ratanmahal Wildlife Sanctuary, the fungi were screened for production of extracellular wood-degrading enzymes on solid media by providing appropriate substrates. The results obtained revealed that 10 fungi were white rot producing microbes with both ligninolytic and cellulolytic ability. Lignocellulolytic behaviour of lignicolus fungi makes them better equipped to degrade different wood in forest area. The white rot fungi showing highest ligninolytic activity was Lenzites exima and lowest cellulolytic activity was recorded in case of L. betulina. The soft rot fungi Phoma multirostrata, Fusarium palidoroseum, Alternaria Alternata, Chaetomium globosum were producing ligninolytic enzyme was reported for the first time.